Inflammasomes and Cancer: The Dynamic Role of the Inflammasome in Tumor Development - Kantono, Melvin; Guo, Beichu (Frontiers in Immunology, 2017)
Chronic Inflammation in tumor microenvironments is not only associated with various stages of tumor development, but also has significant impacts on tumor immunity and immunotherapy. Inflammasome are an important innate immune pathway critical for the production of active IL-1 and IL-18, as well as the induction of pyroptosis. Although extensive studies have demonstrated that inflammasomes play a vital role in infectious and autoimmune diseases, their role in tumor progression remains elusive. Multiple studies using a colitis-associated colon cancer model show that inflammasome components provide protection against the development of colon cancer. However, very recent studies demonstrate that inflammasomes promote tumor progression in skin and breast cancer. These results indicate that inflammasomes can promote and suppress tumor development depending on types of tumors, specific inflammasomes involved, and downstream effector molecules. The complicated role of inflammasomes raises new opportunities and challenges to manipulate inflammasome pathways in the treatment of cancer.